2006
DOI: 10.1080/02640410500131753
|View full text |Cite
|
Sign up to set email alerts
|

Effects of muscle – tendon length on joint moment and power during sprint starts

Abstract: The aim of this study was to examine the effects of muscle-tendon length on joint moment and power during maximal sprint starts. Nine male sprinters performed maximal sprint starts from the blocks that were adjusted either to 40 degrees or 65 degrees to the horizontal. Ground reaction forces were recorded at 833 Hz using a force platform and kinematic data were recorded at 200 Hz with a film camera. Joint moments and powers were analysed using kinematic and kinetic data. Muscle - tendon lengths of the medial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
102
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(129 citation statements)
references
References 10 publications
10
102
0
3
Order By: Relevance
“…Horizontal velocity of the center of mass of athletes were analyzed and concluded that use of starting blocks with 40° angle was resulted in better sprint start performances compared to use of starting blocks with 65° angle. It was stated that 40° angle led to greater muscle-tendon lengths of gastrocnemius and soleus muscles at the onset of the sprint start that resulted in higher ankle joint forces and moments (32). According to this study, these factors played an important role in obtaining a greater block velocity.…”
Section: Studies Investigating Sprint Start Performancementioning
confidence: 86%
See 4 more Smart Citations
“…Horizontal velocity of the center of mass of athletes were analyzed and concluded that use of starting blocks with 40° angle was resulted in better sprint start performances compared to use of starting blocks with 65° angle. It was stated that 40° angle led to greater muscle-tendon lengths of gastrocnemius and soleus muscles at the onset of the sprint start that resulted in higher ankle joint forces and moments (32). According to this study, these factors played an important role in obtaining a greater block velocity.…”
Section: Studies Investigating Sprint Start Performancementioning
confidence: 86%
“…Mero et al (32) showed that maximal rate of force development (highest force generated within the smallest time frame) was crucial in attaining maximal block velocity. Similarly, it was stated that propulsive force applied onto the starting blocks had direct effects on the block velocity and the first phase of acceleration after the sprint start (14,32).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations